An analytical approach for modelling contact forcing function of hailstone impact. (1st May 2023) - Shi, Shuangmin; Lam, Nelson; Chen, Siyu; Cui, Yiwen; Lu, Guoxing; Gad, Emad; Zhang, Lihai
Graphical abstract: Highlights: Analytical model for prediction of forcing function of hail impact is developed. Accuracy of predictions is validated by modified Hopkinson bar experimentation. Analytical modelling circumvents repetitive experiments or FE simulations. Robust model of force–time curves with size-velocity-temperature of hail specified. Structural damage during disintegration of ice into granular pieces is modelled. Abstract: The contact forcing function (of time) generated by the impact of hailstone is crucial to reliable predictions of damage to cladding and glazing panels. This article aims to present the development and validation of an analytical model for predicting this forcing function which is dependent on the size of the hailstone, its temperature, and velocity of impact. The development of this model was justified, as existing analytical models would only give accurate prediction of the peak contact force but not the time history. The newly developed forcing function is divided into two stages: Stage I (the loading phase) which is governed by the effective mass of the hailstone, and Stage II (the unloading phase) which is controlled by the gradual reduction in the stiffness of the disintegrating hailstone. The model has been calibrated against experimental results taken from eight impact tests which employed a modified Hopkinson bar for measurement of the contact force. The simulated predictions have also been validated by comparison against force time curves measured from another 11 impact tests which were independent from the ones employed for the model calibration.